2015
DOI: 10.1177/1464419315569621
|View full text |Cite
|
Sign up to set email alerts
|

Roller bearing dynamics under transient thermal-mixed non-Newtonian elastohydrodynamic regime of lubrication

Abstract: Additional Information:• Abstract:The paper describes a combined tribodynamics analysis (dynamics and contact tribology) of cylindrical roller bearings of a heavy duty truck transmission under high applied loads. The dynamic analysis provides the transient variations in contact load. It also determines the vibration spectrum of the bearing as well as that of contact dynamics. It is shown that with sufficient preloading and/or interference fitting a widely spread loaded region results, which reduces bearing-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 31 publications
(119 reference statements)
0
78
0
1
Order By: Relevance
“…[25][26][27] The effects of generated contact friction and heat generation are also taken into account in some studies. 8,9,28 Therefore, there are many interacting multi-physics issues which affect bearing dynamics, hence the plethora of research work in this area.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] The effects of generated contact friction and heat generation are also taken into account in some studies. 8,9,28 Therefore, there are many interacting multi-physics issues which affect bearing dynamics, hence the plethora of research work in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Under dry conditions, h min U and h min L are eliminated from equation (3). Therefore, the stiffness relationship is written as follows…”
Section: Quasi-static Stiffness For Linear Guideway Considering Dry Cmentioning
confidence: 99%
“…Incorporation of a full numerical solution of the lubricated contact in each step of the dynamic analysis is computationally time consuming, although possible. Therefore, the method used by Mohammadpour et al 3 for roller bearings is followed in this work for linear guideways. This model used an analytical tribological model based on extrapolated oil film formula, incorporated implicitly in the dynamic solution.…”
Section: Introductionmentioning
confidence: 99%
“…The above set of equations (6) to (8) are nonlinear (N R þ 2), second-order differential equations. Rotor mass and its unbalanced effect have been added and no other external load interaction with the system has been considered.…”
Section: Damping Force Calculationmentioning
confidence: 99%
“…Wardle 5 established the analytical model to calculate the force generated due to the surface waviness in a ball bearing and also validate the result with the experiment. Mohammadpour et al 6 analyzed the tribo-dynamic condition of the roller bearing under the effect of non-Newtonian elasto-hydrodynamic lubrication and found that the effect of friction is low reasonably low compared to the dry contact condition. Ehrich 7 developed the relationship between higherorder sub-harmonic vibration responses and rotor speed.…”
Section: Introductionmentioning
confidence: 99%